Ungkapan Visual Perempuan dalam Karya Seni Lukis dari Sudut Pandang Jenny Saville - Zeta Ranniry; Rutnanda Inne Bulu; Fragranthia Jennifer; Vera Liendani; Ariesa Pandanwangi (Ideas Publishing, 2023)
Jenny Saville is a female artist known for highlighting certain body parts in large sizes. The problem is how the visual expression of Jenny Saville s works attracts the attention of many observers of world art, even though her works are presented out of the box. The aim is to reveal the visualization of women from Jenny Saville s point of view using descriptive qualitative methods. His findings include a painting of a woman with a large figure and drawn using pencil, pastel, oil or charcoal with expressive brush strokes (expressive brush strokes with brilliant and contrasting colors). In conclusion, Janne Seville s work has a metaphorical content in conveying a message to appreciators, that her work seems to present a human body that is different from the standards of female beauty in general.